Teknologi-Layanan Keuangan, Literasi-Inklusi Keuangan, dan Value pada Fintech Syariah di Indonesia: Perspektif S-O-R (Stimulus-Organism-Response) Model - Abdillah Ubaidi Djawahir (Proceedings of Annual Conference for Muslim Scholars, 2018)
This paper aims to describe the link between the phenomenon of information technology advancement and financial services, index of literacy and financial inclusion as well as the benefits of Islamic Financial Technology (FinTech) in Indonesia with a Model S-O-R (Stimulus-Organism-Response) perspective. Disruptive Innovation Phenomenon occurs in the Financial Services Industry, an innovation that disrupts the landscape of the Financial Services Industry globally. Starting from the industrial structure, intermediation technology, to the marketing model to consumers. All these changes encourage the emergence of FinTech. Consumer empowerment trilogy has a close relationship in achieving financial well-being. Reading the opportunities and challenges of Fintech Syariah in Indonesia with the perspective of the S-O-R Model, organism moderation toward stimulus and response generates value benefits. Is a benefit for consumers and businesses of Islamic financial services and economy.